Les pintures murals romàniques de Sant Miquel de Cruïlles - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2018)
The author studies, in their historical and iconographic contexts, the remains of the mural decoration of the Benedictine priory of Sant Miquel de Cruïlles, founded by the Cruïlles family and linked to the abbey of Chiusa. On a socle in the apse, against a red background, there are three registers of facing lions, a theme of imperial origins modeled on examples from Constantinople and brought tothe West in the time of the Ottonians. Pictorial vestiges on the upper part of the apse and a fragment of an inscription allow us to infer, according to the author, the iconographic program of the decoration. The Kiss of Judas on the northern arm of the transept would have formed part of a Passion cycle, assuredly culminating in the Crucifixion which would have occupied a position similar to that at Santa Maria de Cervià even though that iconographic program was not the same. The author concludes that the paintings in the apse and transept must be attributed to the same muralist, whose style is like that of the Master of Osomort, derived from the court of Poitiers. The relationship to Poitiers is discussed as well as the possible means for the introduction of this style into Catalonia.